2019
DOI: 10.3390/agronomy9010023
|View full text |Cite
|
Sign up to set email alerts
|

Development of Allergenicity and Toxicity Assessment Methods for Evaluating Transgenic Sugarcane Overexpressing Sucrose–Phosphate Synthase

Abstract: Sugarcane is considered as an industrial crop that produces sugar. The number of transgenic sugarcane on the market is currently increasing. Therefore, investigation of the potential allergens and toxics in transgenic sugarcane is necessary, since there is less information regarding food safety for human consumption. Bioinformatics and experimental analysis were used for the validation of the allergenic potential of transgenic sugarcane overexpressing sucrose–phosphate synthase (SPS). Bioinformatics analysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
1
0
1
Order By: Relevance
“…Contrarily, sucrose synthase activities and their gene expression are substantially higher in young sugarcane internodes, possibly providing carbon for cellulose and cell walls synthesized from uridine-diphosphate-glucose (UDP-G) (Mason et al, 2023). A substantial decrease in SPS-specific activity was exhibited in both varieties, suggesting adverse effects on enzyme functions in sugarcane cultivars due to heat shock treatments, which were also reported in another genotype of sugarcane (Neliana et al, 2019).This finding suggested that sugarcane plants demand optimum temperatures for survival, especially for maximum sucrose accumulation in the stem at the maturity stage. Maximum SPS expression was exhibited at the maturity stage and the correlation analysis showed that the sucrose content had a strongly positive association with SPS.…”
Section: Discussionmentioning
confidence: 75%
“…Contrarily, sucrose synthase activities and their gene expression are substantially higher in young sugarcane internodes, possibly providing carbon for cellulose and cell walls synthesized from uridine-diphosphate-glucose (UDP-G) (Mason et al, 2023). A substantial decrease in SPS-specific activity was exhibited in both varieties, suggesting adverse effects on enzyme functions in sugarcane cultivars due to heat shock treatments, which were also reported in another genotype of sugarcane (Neliana et al, 2019).This finding suggested that sugarcane plants demand optimum temperatures for survival, especially for maximum sucrose accumulation in the stem at the maturity stage. Maximum SPS expression was exhibited at the maturity stage and the correlation analysis showed that the sucrose content had a strongly positive association with SPS.…”
Section: Discussionmentioning
confidence: 75%
“…Enzim yang digunakan dalam uji aktifitas enzim didapatkan dari daun transgenik tomat. Metode ekstraksi mengacu pada Torres et al 1989 dengan sedikit modifikasi (Sawitri et al 2016;Neliana et al 2019). Daun tomat digerus dengan nitrogen cair dan dicampur dengan modifikasi buffer ekstraksi sebanyak 3 kali volum [50mM Tris-HCl (pH 7,5), 150mM NaCl, 1mM MgCl2, 1mM EDTA, 2,5mM DTT dan 10% PVPP].…”
Section: Ekspresi Protein Melalui Aktifitas Enzimunclassified